Does creatine supplementation affect recovery speed of impulse above critical torque? - Abdalla, Leonardo Henrique Perinotto [UNESP]; Broxterman, Ryan Michael; Barstow, Thomas Jackson; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Wiley, 2022)
We previously reported that creatine supplementation improved intermittent isometric exercise performance by augmenting the total impulse performed above end-test torque (total IET′). However, our previous analyses did not enable mechanistic assessments. The objective of this study was to determine if creatine supplementation affected the IET′ speed of recovery. To achieve this objective, we retrospectively analyzed our data using the IET′ balance model to determine the time constant for the recovery of IET′ (τIET′). Sixteen men were randomly allocated into creatine (N = 8) or placebo (N = 8) groups. Prior to supplementation, participants performed quadriceps all-out exercise to determine end-test torque (ET) and IETʹ. Participants then performed quadriceps exercise at ET + 10% until task-failure before supplementation (Baseline), until task-failure after supplementation (Creatine or Placebo), and until the Baseline time after supplementation (Creatine- or Placebo-Isotime). τIET′ was faster than Baseline for Creatine (669 ± 98 vs 470 ± 66 s), but not Placebo (792 ± 166 vs 786 ± 161 s). The creatine-induced change in τIET′ was inversely correlated with the creatine-induced changes in both the rate of peripheral fatigue development and time to task-failure. τIET′ was inversely correlated with total IET′ and ET in all conditions, but creatine supplementation shifted this relationship such that τIET′ was faster for a given ET. Creatine supplementation, therefore, sped the recovery of IET′ during intermittent isometric exercise, which was inversely related to the improvement in exercise performance. These findings support that the improvement in exercise performance after creatine supplementation was, at least in part, specific to effects on the physiological mechanisms that determine the IET′ speed of recovery. HIGHLIGHTS Sixteen healthy participants were randomly allocated to creatine supplementation or placebo groups. Creatine supplementation accelerated the time constant for the recovery of IET′ (τIET′). The time constant for the recovery of IET′ (τIET′) was inversely related to both the rate of peripheral fatigue development and the time to task failure.
Keywords: creatine; Exercise tolerance; recovery; severe-intensity domain